Savanização antrópica de ambientes no semiárido pernambucano - França, Elaynne Mirele Sabino de (2023)
The anthropic alteration of natural spaces, in an unrestricted and constant way, has been contributing to disturbances in the ecological framework. This aspect introduced with the suppression or conversion of vegetation in the semi-arid environment, of heterogeneous character, installs the core for environmental degradation of lands with forest formation and rugged Caatinga. Thus, the monotony of landscapes supports the understanding of spaces subject to anthropic savannization due to the phytophysiognomic and geoecological transformation. Within the context, the present research aimed to analyze the bioclimatic and anthropic interactions as promoters for modification and or intensification of the savannization process in the semi-arid region of Pernambuco. The systemic approach was taken as a theoreticalmethodological contribution, as it constitutes an element for analyzing the complexity of the landscape, guided by the structural and anthropogenic dimensions. In addition to the use of digital processing techniques and data elaboration with the aid of geotechnologies and field activities. The area is characterized by a hydrothermal regime in three types of climate, namely: Subhumid, Subhumid Dry and Semi-arid. In which it receives the influence of meteorological-climatic systems that interfere in the variability of precipitation, in view of the annual behavior and water balance. Furthermore, it provides conditions for the occurrence of biotic elements such as vegetation, in the case researched, of forest and savannah formation with deciduous xerophytic seasonal characteristics. Thus, the dynamic climate, vegetation and associated anthropic action interfere in biogeochemical processes of self-regulation of the natural system. Even land use and land cover showed evidence regarding the environmental status of the landscape and warns of signs of degraded spaces, that is, an environment with hot thermal conditions, semi-arid, with the presence of soils that are highly susceptible to weathering processes, of the order physical, and which experienced changes to the pasture area and crops to the detriment of vegetation cover.